Talent Scouting sebagai Pengarah pada Kegiatan Positif melalui Penyelenggaran Turnamen Bola Voli - Santika Rentika Hadi; Bambang Juni Pitoyo; Catur Erik; Yandika Fefrian Rosmi; Achmad Nuryadi; Mulyono Mulyono; Brahmana Rangga; Ongky Airlangga (Jurnal Pengabdian Pada Masyarakat, 2021)
TALENT SCOUTING AS A DIRECTION FOR POSITIVE ACTIVITIES THROUGH ORGANIZING VOLLEYBALL TOURNAMENTS. The sport potential in Gondang sub-district in general and in Kalikatir village in particular is the Volleyball game. On the other hand juvenile delinquency is a challenge that must be faced. The implementation of the Vaoli Ball tournament Tournament Cup at the PGRI Adi Buana University Surabaya is an activity forum that is expected to be used as a talent scoating for volleyball players and can provide a focus of positive activities for villagers, especially young people, to be directed towards positive activities, so as to prevent the possibility of the possibility of unwanted negative activity. The Rector Cup Volleyball Tournament of PGRI Adi Buana University Surabaya was held from February 19 to February 27, 2020, in Kalikatir Village with 16 Village participants in Gondang District, Mojokerto Regency. The tournament uses the knockout system. Monitoring of talented young players can be used as a guideline for coaching program planning at the Gondang District level. Observation about the sustainability of the program through interviews and questionnaires to explore the interest and commitment to volleyball. The results achieved, as the first winner was Bening village, 2nd place Kalikatir village, 3rd place Wonoploso village and 4th place Kemasantani village. The recruitment of 13 young players, and 2 senior players with adequate volleyball ability, are ready to be selected to become the Gondang District team. Commitment to continuing to practice volleyball and keep yourself from negative things to achieve. An awareness of the benefits of high-performance sports can support the future of volleyball players.